103k views
5 votes
Use f(x) = 3 - 2x2 - 2x and g(x) = 8x - 5 to determine (f-g)(x) then write in standard form

User Claret
by
5.2k points

1 Answer

3 votes

(f-g)x=-2x^2\text{ - 10x + 8}

Here, we are given two functions and we want to find the difference between the two functions;

Looking at what we have;

(f-g)x

What this mean is that we are to subtract g(x) from f(x);

Mathematically;


\begin{gathered} (f-g)x\text{ = f(x) - g(x)} \\ \\ =3-2x^2-2x\text{ - (8x - 5)} \\ \\ =3-2x^2-2x-8x\text{ + 5} \\ \\ =3+5-2x-8x-2x^2 \\ \\ =8-10x-2x^2 \\ \\ (f-g)x=-2x^2\text{ - 10x + 8} \end{gathered}

User Ole Dittmann
by
4.9k points